The End of "The End of History" - One Tale, Two Continents - Szántó, Diána (Modern Africa: Politics, History and Society, 2016)
This paper’s objective is to give an account of the ongoing transition from liberal democracy to a new form of governance, defined by the Hungarian Prime-Minister, Viktor Orbán, as the “illiberal state.” The author examines the transformation of the political culture in two countries, which at first sight do not have much in common: Sierra Leone and Hungary. In order to better understand the nature, causes and possible consequences of this shift, she re-examines the path leading from the democratic transformation of the 1990s to the present-day changes. She concludes that the move towards illiberal democracy is not a sudden, irrational deviation from what preceded it but rather the direct consequence of the way democratization was conceived and implemented in the countries in question. From a local angle, the illiberal turn points at a double rupture: that of the contract between national governments and local civil societies. From a global perspective, it probably reflects a tectonic reorganisation of international power relations.